PENGARUH MOTIVASI USAHA DAN KEMAMPUAN USAHA DALAM MENINGKATKAN KEBERHASILAN USAHA - Siti Nur Azizah (P4M STIE Putra Bangsa, 2013)
This study aimed to examine the effect of motivation and the ability of businesses to the success of business (case study of micro business, sate merchants in Candiwulan Village, Kebumen). This research is explanatory research. The population in this study is the SME entrepreneurs sate merchants in Candiwulan Village, Kebumen and sampling methods used are saturated samples with the number of respondents as many as 43 people. The analytical method used is path analysis. The results showed that positive effect of business motivation on the capability of business but business capabilities does not affect the business success of sate merchants in Candiwulan Village, Kebumen, so that the necessary efforts to improve the ability of business